Futurological explanations of the new ukrainian educational policy - Nezhyva, Olga (My University, 2022)
The article considers the peculiarities of futurological explications of the new educational policy in Ukraine. It also shows the existing contradictions in the development of the state education policy of Ukraine and the importance for transitive societies of its formation on a democratic basis, actualizing the development and implementation of the policy of reforming the national education system. At the same time, the peculiarities of the formation and development of the Soviet and European education system are analyzed. Each of them has certain advantages and disadvantages. The article notes that educational policy should move away from monosubjectivity and become polysubjective. To do this, it should be based not only on state, but also on public, social mechanisms of activity regulation, create and maintain a favorable environment for the existence and functioning of alternative opportunities, which is a necessary condition for the establishment of free educational interaction and the understanding of education as a practice of freedom. The article illustrates the main provisions of the Ukrainian educational policy based on the Ukrainian national idea. These provisions provide for the following: Ukrainian educational policy should be based on the recognition of the fact of the birth of individuality, as well as be based on the principle of "do no harm"; an individual approach to pupils and students requires certain changes in the organization of the system; relevance of the language issue in education; it is necessary to establish independent public control over the quality of educational services provided and their compliance with modern world standards; it is necessary to move away from the cult of the received diploma, and it is also necessary to strive for constant professional growth of all categories of the population: from teachers to motorists. The article illustrates the main provisions of the Ukrainian educational policy based on the Ukrainian national idea. These provisions provide for the following: Ukrainian educational policy should be based on the recognition of the fact of the birth of individuality, as well as be based on the principle of "do no harm"; an individual approach to pupils and students requires certain changes in the organization of the system; relevance of the language issue in education; it is necessary to establish independent public control over the quality of educational services provided and their compliance with modern world standards; it is necessary to move away from the cult of the received diploma, and it is also necessary to strive for constant professional growth of all categories of the population: from teachers to motorists. And this growth should be accompanied by diplomas obtained, and from educational institutions of authority not only in Ukraine, but also abroad. Besides, this growth should be accompanied by diplomas obtained, and from educational institutions of authority not only in Ukraine, but also abroad. У статті розглядаються особливості футурологічних експлікацій нової української освітньої політики. Також показано наявні протиріччя розвитку державної освітньої політики України та важливість для транзитивних суспільств формування її на демократичних засадах актуалізує розроблення й упровадження політики реформування національної системи освіти. При цьому аналізуються особливості формування і розвитку радянської і європейської системи освіти. Кожна з них володіє певними перевагами і недоліками. У статті відзначено перспективи переходу від моносуб’єктності до полісуб’єктності освітньої політики. Для цього потрібно, щоб освітня політика ґрунтуватися не тільки на державних, а й на громадських, суспільних механізмах регулювання діяльності, створювати та підтримувати сприятливе середовище для існування та функціонування альтернативних можливостей, що є необхідною умовою утвердження вільної освітньої взаємодії та розуміння освіти як практики свободи. Стаття ілюструє основні положення української освітньої політики, заснованої на українській національній ідеї. Ці положення передбачають наступне: українська освітня політика повинна базуватися на визнанні факту народження індивідуальності, а також, будуватися за принципом «не нашкодити»; індивідуальний підхід до учнів і студентів вимагає певних змін в організації системи; освіти актуальність мовного питання; необхідно налагодити незалежний громадський контроль над якістю освітніх послуг, що надаються та їх відповідності сучасним світовим стандартам; потрібно відійти від культу отриманого диплому, а також, необхідно домагатися постійного професійного зростання всіх категорій населення: від учителів до автомобілістів. І це зростання має супроводжуватися отриманими дипломами, причому освітніх установ авторитетних не тільки в Україні, а й за її межами.
Keywords: кафедра іноземних мов професійного спрямування; education; education system; reform; university; policy; futurological explanation; освіта; система освіти; реформа; університет; політика; футурологічна експлікація